MicroRNA124-IL6R Mediates the Effect of Nicotine in Inflammatory Bowel Disease by Shifting Th1/Th2 Balance Toward Th1 - Qin, Zhen; Wang, Peng-Yuan; Wan, Jing-Jing; Zhang, Yu; Wei, Jie; Sun, Yang; Liu, Xia (Frontiers in Immunology, 2020)
Epidemiological investigations have shown that smoking ameliorates ulcerative colitis (UC) but exacerbates Crohn's disease (CD), diseases that feature a Th2-mediated and Th1-mediated response, respectively. Cigarette extracts, especially nicotine, affect the Th1/Th2 balance. We previously reported that nicotine protects against mouse DSS colitis (similar to UC) by enhancing microRNA-124 (miR-124) expression. Intriguingly, elevation of miR-124 in CD is reported to aggravate the disease. Here we investigate the dual regulation of miR-124 in inflammatory bowel diseases (IBDs), which may explain the similar bidirectional regulation of tobacco. We found that overexpressed miR-124 protected against mouse DSS-induced colitis with a Th1 polarization in peripheral blood lymphocytes and colon tissues, which was also found in human peripheral blood lymphocytes. Conversely, miR-124 knockdown worsened DSS murine colitis with a Th2 polarization. Moreover, knockdown of miR-124 could eliminate the polarization toward Th1 after nicotine treatment, suggesting that miR-124 mediates the effect of nicotine on the Th1/Th2 balance. In addition, interference of IL-6R, which is a downstream target of miR-124, could remarkably weaken the Th1 polarization induced by miR-124. Taken together, these results suggest that nicotine shifts the balance of Th1/Th2 toward Th1 via a miR-124-mediated IL-6R pathway, which might explain its dual role in IBDs.